Untuk Meningkatkan Hasil Belajar Bahasa Indonesia Siswa Kelas I SD Muhammadiyah 2 Kabupaten Maros dengan Penggunaan Model Pembelajaran Kooperatif Tipe STAD - Despryanto Despryanto (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
The Professional Strengthening Program for Teachers (P2K) implemented at SD Muhammadiyah 2 Maros aims to improve students' teaching skills through a practical approach. This classroom action research (CAR) focuses on the application of the STAD (Student Teams Achievement Divisions) cooperative learning model to improve the early reading skills of grade I students. The learning process is carried out in two cycles that include planning, implementing actions, observation, and reflection. The results of the study indicate that the use of letter card media is effective in increasing active student participation, learning interest, and student learning outcomes, as indicated by an increase in the average score from the first cycle to the second cycle. This study emphasizes the importance of innovation in learning strategies, especially through the use of simple interactive media, to overcome the challenges of student heterogeneity at the elementary school level.